Foundations in microbiology : (McGraw-Hill, 2008)
Written with the non-major/allied health student in mind, Foundations in Microbiology: Basic Principles offers an engaging and accessible writing style through the use of tools such as case studies and analogies to thoroughly explain difficult microbiology concepts. This version includes chapters 1 through 17 of the full Foundations in Microbiology text, teaching only the basic principles of microbiology and not covering the clinical aspects.